Test Performance of Plastic Waste Shredder Machine and Analyze the Quality of the Shredded Plastic Product Using the Taguchi Method - Adam - Kamil; Hendra Hendra; Sidik Susilo; Erny Listijorini; Hernadewita Hernadewita (Department of Mechanical Engineering, Universitas Andalas, 2022)
The food and beverage industry contributes 65% to the total plastic packaging demand and also produces plastic waste. This causes problems for the environment, humans, and others, especially in the waste treatment process. Because plastic is difficult to recycle by the soil or the environment. Consumption of plastic packaging also reaches 65% of the total national plastic consumption. To overcome this plastic processing, a plastic Waste processing machine is made that can process and change the form of plastic waste into other derivative products. The important thing in plastic processing machines is the ability of plastic processing machines to produce products according to consumer desires. The purpose of this research is to get the maximum capacity of plastic Waste shredding, and to know the production capacity of plastic waste in one process of enumeration. The experiment method is used in this research to get the performance of the machine like voltage, power, cutting force of tool, and cutting speed. Also Taguchi method are used to analyze of quality product by varying shape of product waste plastic such as cup, bottle and gallon cap. In this test, a maximum capacity of 20Kg/hour was obtained by using the plastic gallon cap test material. By calculate of cutting force for gallon cap is obtained voltage 231.5 Volts and power 555,4 Watts at shaft rotation 24,96 rpm. Cutting force of tool is 25,92 N and torque 1,68Nm with cutting speed of 1.986 m/min. For cup plastic obtained, the results on voltage are 238.9 Volt and power 585,96 Watts by a shaft rotation of 25,1 rpm. The cutting force of the tool is 54 N and torque 3.36 Nm with a cutting speed of 2.025m/min. For the plastic bottle, the Voltage is 238.86 Volt and the power of 595.9 Watts at the shaft rotation is 24,8rpm. Cutting force of tool is 119.23 N and torque is 7.75 Nm at the cutting speed is 1.97m/min.